The Mitochondrial Ca2+ Uptake and the Fine-Tuning of Aerobic Metabolism - Gherardi, Gaia; Monticelli, Halenya; Rizzuto, Rosario; Mammucari, Cristina (Frontiers in Physiology, 2020)
Recently, the role of mitochondrial activity in high-energy demanding organs and in the orchestration of whole-body metabolism has been receiving renewed attention. In mitochondria, pyruvate oxidation, ensured by efficient mitochondrial pyruvate entry and matrix dehydrogenases activity, generates acetyl CoA that enters the TCA cycle. TCA cycle activity, in turn, provides reducing equivalents and electrons that feed the electron transport chain eventually producing ATP. Mitochondrial Ca2+ uptake plays an essential role in the control of aerobic metabolism. Mitochondrial Ca2+ accumulation stimulates aerobic metabolism by inducing the activity of three TCA cycle dehydrogenases. In detail, matrix Ca2+ indirectly modulates pyruvate dehydrogenase via pyruvate dehydrogenase phosphatase 1, and directly activates isocitrate and α-ketoglutarate dehydrogenases. Here, we will discuss the contribution of mitochondrial Ca2+ uptake to the metabolic homeostasis of organs involved in systemic metabolism, including liver, skeletal muscle, and adipose tissue. We will also tackle the role of mitochondrial Ca2+ uptake in the heart, a high-energy consuming organ whose function strictly depends on appropriate Ca2+ signaling.